1991
DOI: 10.1620/tjem.165.49
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Adenosine on Canine Penile Erection.

Abstract: We investigated the pharmacological effects of adenosine on canine penile erection in vivo. Intracavernous injection of adenosine induced a full erection, which was unaffected by hexamethonium and atropine. The erectile response induced by adenosine was augmented by intracavernous pretreatment with dipyridamole and markedly depressed by theophylline. The erectile response induced by cavernous nerve stimulation was also enhanced by dipyridamole and reduced by theophylline. The combination of acetylcholine and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This effect, which was unaffected by atropine and hexamethonium, could be obtained with no changes in systemic blood pressure. In addition, adenosine produced full erection on intracavernosal administration [25].…”
Section: Discussionmentioning
confidence: 92%
“…This effect, which was unaffected by atropine and hexamethonium, could be obtained with no changes in systemic blood pressure. In addition, adenosine produced full erection on intracavernosal administration [25].…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports demonstrated that intracavernous injection of adenosine induces full erection in dogs (Takahashi et al, 1992) and that the erectile response induced by cavernous nerve stimulation is enhanced by the adenosine uptake inhibitor dipyridamole (Takahashi et al, 1991). In the rabbit corpus cavernosum, adenosine has potent relaxant activity, acting through the A2 A receptor subtype (Mantelli et al, 1995) and it also modulates both adrenergic and NANC neurotransmission (Chiang et al, 1994).…”
Section: ϫ8mentioning
confidence: 99%
“…Intracavernosal injection of adenosine induced a full erection in cats [394,395]. Adenosine also had prejunctional inhibitory actions on excitatory sympathetic cotransmission to the rabbit corpus cavernosum, probably acting via A 2B receptors [79].…”
Section: Penis and Penile Erectionmentioning
confidence: 99%